Experimental Study of A Vacuumed Solar Still System - Omar Badran; Nabil Beithou; Aiman Al Alawin; Ahmad Awad; Yaser Abdelhadi; Anwar Al-Mofleh (Institute of Advanced Engineering and Science, 2013)
This experimental study presents a thermal design of a passive solar water distillation system with vacuum. The designed model consists of a glass cover, basin water equipped with reflecting mirror and insulation, and controlled vacuum pump to create vacuum inside the still to decrease the saturation temperature of water and in order to increase the yield. Feed water in the basin is heated by solar energy, and the evaporated water is condensed by inner glass cover. The temperatures at different locations in the system, the received amount of solar radiation, and the distilled water produced were determined. The highest temperature developed inside the distilling device was 51˚ C at ambient temperature of 24˚ C, the daily water production was 1.2 L/m2.day, and the efficiency of the solar still was 15%.